Cross-correlation properties between GMW and WG sequences and that of WG sequences - TONG Xin; WEN Qiao-yan (Tongxin xuebao)
For odd n,the cross-correlations between Gordon-Mills-Welch（GMW） sequences and Welch-Gong（WG） sequences（decimated WG sequences with one particular exponent） and that of WG sequences were investigated.It shows that the calculations of the cross-correlation between GMW sequences and WG sequences（decimated WG sequences with one particular exponent） and that of WG sequences were all related to the cross-correlation of m-sequences and their decimations.Moreover,the cross-correlation of WG sequences can be 3-valued or 5-valued under a certain condition.Furthermore,the maximum magnitude of the cross-correlation between GMW sequences and WG sequences were given.